On the Exterior Degree of a Finite-Dimensional Lie Algebra - Afsaneh Shamsaki; Mohsen Parvizi; Ahmad Erfanian (Journal of Mathematics)
In this paper, we define the exterior degree for a finite-dimensional Lie algebra over the field Fq and give upper and lower bounds. Also, we give some relations between this concept and commutativity degree, capability, and Schur multiplier.